Biosynthesis of 4-Thiouridine in tRNA in the Methanogenic Archaeon Methanococcus maripaludis - Liu, Yuchen (American Society for Biochemistry and Molecular Biology, 2012)

(untitled)
4-Thiouridine (s(4)U) is a conserved modified nucleotide at position 8 of bacterial and archaeal tRNAs and plays a role in protecting cells from near-UV killing. Escherichia coli employs the following two enzymes for its synthesis: the cysteine desulfurase IscS, which forms a Cys persulfide enzyme adduct from free Cys; and ThiI, which adenylates U8 and transfers sulfur from IscS to form s(4)U. The C-terminal rhodanese-like domain (RLD) of ThiI is responsible for the sulfurtransferase activity. The mechanism of s(4)U biosynthesis in archaea is not known as many archaea lack cysteine desulfurase and an RLD of the putative ThiI. Using the methanogenic archaeon Methanococcus maripaludis, we show that deletion of ThiI (MMP1354) abolished the biosynthesis of s(4)U but not of thiamine. MMP1354 complements an Escherichia coli ΔthiI mutant for s(4)U formation, indicating that MMP1354 is sufficient for sulfur incorporation into s(4)U. In the absence of an RLD, MMP1354 uses Cys(265) and Cys(268) located in the PP-loop pyrophosphatase domain to generate persulfide and disulfide intermediates for sulfur transfer. In vitro assays suggest that S(2−) is a physiologically relevant sulfur donor for s(4)U formation catalyzed by MMP1354 (K(m) for Na(2)S is ∼1 mm). Thus, methanogenic archaea developed a strategy for sulfur incorporation into s(4)U that differs from bacteria; this may be an adaptation to life in sulfide-rich environments.